2019
DOI: 10.1080/13697137.2018.1551346
|View full text |Cite
|
Sign up to set email alerts
|

Benefit–risk profile of black cohosh (isopropanolic Cimicifuga racemosa extract) with and without St John’s wort in breast cancer patients

Abstract: Endocrine therapy in breast cancer survivors can cause severe 'climacteric' symptoms, which may compromise therapy adherence. To determine whether such symptoms can be treated with herbal medication containing black cohosh in the form of isopropanolic Cimicifuga racemosa extract (iCR) alone or in fixed combination with St John's wort (Hypericum perforatum [HP]) (iCR þ HP), a systematic literature search was conducted. Results were viewed in relation to experimental data and metabolism of endocrine therapies. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
37

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 78 publications
(113 reference statements)
0
18
0
37
Order By: Relevance
“…About this, we have published elsewhere. 38 Regarding a possible association between menopausal symptoms and other related factors, which were investigated in our study, we found that current smoking, gravidity, parity, and menarche are not related to menopausal symptoms. We only found that alcohol consumption (≥3times/week) could aggravate VMS.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…About this, we have published elsewhere. 38 Regarding a possible association between menopausal symptoms and other related factors, which were investigated in our study, we found that current smoking, gravidity, parity, and menarche are not related to menopausal symptoms. We only found that alcohol consumption (≥3times/week) could aggravate VMS.…”
mentioning
confidence: 53%
“…This is in line with the results of Freeman et al, who found a significant positive association between alcohol intake and hot flashes. 38 However, the results in the SWAN study did not detect any effects of alcohol consumption on VMS. 39 This and other differences can be explained as we performed simple and unconditional logistic regression methods with rigorous adjustment of all analyzed factors, with the consequence that we obtained similar results to other studies for some of those single factors in the "Crude OR", ie, significant relationships, but not after multiple adjustments.…”
mentioning
confidence: 85%
“…53,54 • Specific dietary supplements, such as a fixed combination of black cohosh (isopropanolic Cimicifuga racemosa extract) and St John's wort. 55 • Gabapentin. 54,56,57 • Clonidine.…”
Section: Premature Infertility and Menopausal Symptomsmentioning
confidence: 99%
“…54,58,59 • Appropriate selective serotonin reuptake inhibitors (SSRIs; note that some SSRIs, such as paroxetine and fluoxetine, are likely to interfere with the metabolism of tamoxifen, resulting in reduced production of its main active metabolite, and should be avoided when patients are on this ET). 54,55,[58][59][60][61] • Oxybutynin (Table 4). 54,62,63 • Stellate ganglion block (limited supporting study data, but case reports/series indicate that there are some patients for whom nothing else works and for whom this option provides relief).…”
Section: Premature Infertility and Menopausal Symptomsmentioning
confidence: 99%
“…However, further studies, especially clinical trials, are required to confirm this. Further recommendations include weight loss (for achieving an effect, 10% decrease in the usual weight is required) and the administration of Cimicifuga racemosa, eventually in combination with St John's Wort in cases with reduced auxiliary mood swings [26].…”
Section: "Integrative Medicine" For the Treatment Of Side Effects Of mentioning
confidence: 99%